An indefensible frontier: the Claustra Alpium Iuliarum - Poulter, Andrew G. (Österreichisches Archäologisches Institut, 2013)
It has been long maintained that the system of barrier walls and fortlets in the Julian Alps dates to the early 4th century and that it was a fortification line used to defend Italy during times of civil war. Reviewing the historical, archaeological and topographic evidence, it is here argued that its military importance has been much exaggerated; one role may well have been to regulate traffic and perhaps to exact taxes from the civilians using the imperial road system, or crossing from Illyricum into Italy. Its date cannot be yet established for certain but the most likely context is the very end of the 4th century AD, not long before the system was abandoned at some point during the first decade of the 5th century. Contrary to received wisdom, it was incapable of repulsing any major force coming from the East, whether they were Goths or Romans. Regulation and taxation, however, do not require the erection of barrier walls. There must have been additional reasons for their construction even though the walls were unable to deal with anything more than a low intensity threat. What the percieived danger was, it is impossible to determin for certain,except that there were a series of problems facing the Western Empire c. 390-400 which could warrant the construction of a 'frontier' in the Julian Alps; an influx of refugees from Illyricum, Gothic war bands from Thrace, raiding parties from across the Danube and the endemic danger posed by local bandits. Any one of these, or more likely a combination of several factors, precipitated the decision to regulate, but not seriously to defend the routes which led west from Illyricum and into the Italian peninsular.